Large scale cultivation of microalgae at Finnfjord AS: The effect of different storage treatments on lipid and fatty acid stability - Aronsen, Simen (UiT Norges arktiske universitet, 2018)
The Arctic University of Norway and the ferrosilicon smeltery Finnfjord AS has started a microalgal mass cultivation project where sequestration of CO2 and NOx from factory fumes are used in the production of diatom biomass. Primary application of the produced biomass is fish feed. This requires information regarding lipid content and storage stability. In this study the lipid content, fatty acid composition and the effect of different storage treatments (formic acid, benzoic acid and heat) were investigated for the diatom species Porosira glacialis. The diatoms were cultivated at the factory facilities at Finnfjord AS in Finnfjordbotn. The lipids were extracted using Folch’s method with some modifications, and the lipid content was determined gravimetrically. The lipids were transesterified to yield isolated fatty acids methyl esters (FAMEs) which was quantified by GC-MS. To investigate the double bond positions of the fatty acids, the FAMEs were further transesterified to 3-pyridylcarbinol esters and analyzed by GC-MS. A total of 20 different fatty acids were identified. Double bond position of all fatty acids except 18:3 were determined. The fatty acid composition of P. glacilis is highly unsaturated with roughly 80% poly unsaturated fatty acids. These essentially consist of 16:4 (n-1) and EPA (20:5 n-3). Low amounts of omega-6 fatty acids (<1%) were found. The low omega-6 to omega-3 ratio is favorable and makes P. glacilis a candidate for fish feed production. Heat treatment seem to be the most promising treatment of the ones tested. 14 days of storage at 4ºC and 20 ºC did not influence the extracted lipid content and fatty acid composition remarkably. Generally, results from the lipid content analysis were conflicting. Hence the analysis should be repeated.